Observations on Early and Delayed Colostomy Closure - A O Tade; B A Salami; B A Ayoade (Nigerian Postgraduate Medical Journal, 2011)
Background: T raditional treatment of a variety of colorectal pathologies had included a diverting colostomy that was closed eight or more weeks later during a readmission. Aims and objectives: The aim of this retrospective study was to determine the outcomes of early colostomy closure and delayed colostomy closure in patients with temporary colostomies following traumatic and non-traumatic colorectal pathologies. In this study early colostomy closure was the closure of a colostomy within three weeks of its construction, while delayed colostomy closure referred to closure after 3 weeks. Patients and methods: Complete records of the 37 adult patients who had temporary colostomy constructed and closed between Jan. 1997 December 2003 for various colorectal pathologies were studied. Results: Fourteen patients had early colostomy closure while 23 had delayed closure. In the early colostomy closure group there were 10 men and 4 women. The mean age of the patients was 28yr with a range of 18 - 65yr. Colostomies were closed 9 - 18days after initial colostomy construction. There was no mortality. Morbidity rate 28.6% (4 out of 14). There were two faecal fistulas (14.3%). Twenty-three patients had delayed colostomy closure 8 weeks to 18 months after initial colostomy construction. These were patients unfit for early surgery after initial colostomy construction because of carcinoma, significant weight loss, or sepsis. There was no mortality. Morbidity rate was 26.1%. There were 3 faecal fistulas (13.2%). Conclusion: Outcomes following early colostomy closure and delayed closure were comparable. Patients fit for surgery should have early closure whilst patients who may have compromised health should have delayed closure.